Association between MDM2 SNP309, p53 Arg72Pro, and hepatocellular carcinoma risk: A MOOSE-compliant meta-analysis. Issue 36 (September 2017) - Duan, Xiaohua; Li, Jingquan
Abstract : Abstract: Epidemiological studies have determined the associations between polymorphisms on the promoter of MDM2 (SNP309) and the codon 72 on exon 4 of p53 (p53 Arg72Pro) and the risk of hepatocellular carcinoma (HCC); however, the results were not always consistent. The aim of the present meta-analysis was to evaluate the overall associations between these 2 variants and HCC risk. The MEDLINE, Web of science, EMBASE, Cochrane Library, and CNKI databases were searched for eligibility studies and the data were synthesized under the fixed- or random-effects model. Heterogeneity among the studies was evaluated with the Cochrane test Q and I 2 statistic. For MDM2 SNP309, the pooled odds ratio (OR) from 15 independent studies with a total of 4038 cases and 5491 controls suggested a significant association for the variant with HCC risk [allele model, G vs T: pooled OR = 1.48, 95% confidence interval (95% CI) = 1.26–1.73; pooled OR = 1.53, 95% CI = 1.26–1.81, for G/T vs T/T; pooled OR = 2.04, 95% CI = 1.54–2.71 for G/G vs T/T]. For p53 Arg72Pro, a total of 21 studies with 7285 cases and 9710 controls suggested that the variant was also associated with HCC risk under common genetic model (allele Pro vs Arg, pooled OR = 1.13, 95% CI = 1.02–1.25; Pro/Pro vs Arg/Arg, pooled OR = 1.32, 95% CI =1.06–1.64). No publication bias was found for all the meta-analysis as suggested by the Begg funnel plot and Egger tests. These results suggested that variants MDM2 SNP309 and p53 Arg72Pro are susceptibility factors for HCC; however, more studies are warranted to validate the results.